The prevalence and predictors of geriatric giants in community-dwelling older adults: a cross-sectional study from the Middle East - Seyedeh Zahra Badrkhahan; Moein Ala; Hossein Fakhrzadeh; Arash Yaghoobi; Sara Mirzamohamadi; Seyed Masoud Arzaghi; Sina Shahabi; Farshad Sharifi; Afshin Ostovar; Noushin Fahimfar; Iraj Nabipour; Bagher Larijani; et al. (Scientific Reports, 2023)
Abstract The term “geriatric giants” refers to the chronic disabilities of senescence leading to adverse health outcomes. This study aimed to investigate the prevalence and predictors of geriatric giants in Southern Iran. The participants were selected from Bushehr city using a multistage cluster random sampling method. Demographic data were collected through interviews. Frailty, incontinence, immobility, depression, cognitive impairment, and malnutrition were measured by questionnaires and instruments. Finally, data from 2392 participants were analyzed. The prevalence of fecal incontinence was less than 1% among all participants and similar in men and women. In contrast, compared with men, women had higher prevalence of urinary incontinence (36.44% vs. 17.65%), depression (39.05% vs. 12.89%), anorexia and malnutrition (2.35% vs. 0.82%), immobility (8.00% vs. 2.5%), frailty (16.84 vs. 7.34), and pre-frailty (54.19 vs. 38.63%). The prevalence of dependence and cognitive impairment was also higher in women and considerably increased with the age of participants. In total, 12.07% of subjects were frail, and 46.76% were pre-frail. The prevalence of frailty exponentially increased in older age, ranging from 4.18% among those aged 60–64 years to 57.35% in those aged ≥ 80 years. Considering 95% confidence interval (CI), multivariate logistic regression revealed that low physical activity [odds ratio (OR) 31.73 (18.44–54.60)], cancer (OR 3.28 (1.27–8.44)), depression [OR 2.42 (1.97–2.98)], age [OR 1.11 (1.08–1.14)], waist circumference [OR 1.03 (1.01–1.06)], BMI [OR 1.07 (1.01–1.14)], MNA score [OR 0.85 (0.79–0.92)], polypharmacy [OR 2.26 (1.30–3.95)] and male gender [OR 0.63 (0.42–0.93)] were independently associated with frailty. White blood cell count (WBC), smoking, marital status, and number of comorbidities were not independently associated with frailty. Low physical activity was the strongest predictor of frailty, which may need more attention in geriatric care. Frailty, its predictors, and other components of geriatric giants were considerably more common among women and older ages.